Translating “Interjections, Exclamations dan Phatic Expressions” from Indonesian Literature into English - Erna Wiles (Universitas Veteran Bangun Nusantara, 2020)
Due to their uniqueness, which among others are having various forms (particles, morphemes, words, phrases, minor and extra-sentences), different form of part of speech, containing connotative, emotive or affective, and social-stylistic meanings, culturally-bound, etcetera, it is quite challenging to translate interjections, exclamations and phatic communions from one language to another, especially when it involves literary work. To discover the most effective strategies, analysis was conducted by comparing BumiManusiaby Pramoedya Ananta Toer with its English translation ‘This Earth of Mankind’ by Max lane. To gain the optimum meaning transportation, interjections, exclamations and phatic communions especially those containing socio-cultural meaning, those which has been archaic, universally used and understood, and any interjections, exclamations and phatic communions written in other language than that of source text should be retained. The spelling and the orthography can be adjusted to target language system if necessary andwhen the context allows. Any interjections, exclamations and phatic communions which have equivalent in target language have to be translated. Those with no equivalents should be retained as they are. For clarity,extra information can be added on their first appearance. On their second appearance onward, they can be retained. It is sometimes wise to translate them into a different part of speech.